2012
DOI: 10.1016/j.chemgeo.2012.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The partitioning of transitional metals (Fe, Mn, Ni, Cr) in mangrove sediments downstream of a ferralitized ultramafic watershed (New Caledonia)

Abstract: In New Caledonia, one third of the Island is composed of ultramafic rocks, and lateritic soils enriched in Fe, Ni and Cr. Open-cast mining occurs all around the Island, and processes of erosion and sedimentation, which occur naturally along the coastline, are strongly amplified by mining activities. Due to their position, at the interface between land and sea, mangroves receive extensive amounts of particles emanating from rivers through estuaries. The purpose of this study is to understand the distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 64 publications
5
77
2
1
Order By: Relevance
“…The geochemical behavior of Mn and Fe in estuarine environments certain order of redox sequence (Marchand et al 2006(Marchand et al , 2012. Fe and Mn concentrations were highest in F5 fraction followed by F3 and F4 fractions in surface sediments and cores.…”
Section: Total Cr Concentration Increased By Approximately Five Foldsmentioning
confidence: 96%
See 2 more Smart Citations
“…The geochemical behavior of Mn and Fe in estuarine environments certain order of redox sequence (Marchand et al 2006(Marchand et al , 2012. Fe and Mn concentrations were highest in F5 fraction followed by F3 and F4 fractions in surface sediments and cores.…”
Section: Total Cr Concentration Increased By Approximately Five Foldsmentioning
confidence: 96%
“…Notably, these metals can accumulate in mangrove plant tissues, and pose long-term damaging effects in the food chain through biomagnification (Agoramoorthy et al 2008;Tam and Wong 2000). Hence, metal cycling in different mangrove ecosystems has been addressed by many authors (Furukawa et al 1997;Yim and Tam 1999;Tam and Wong 2000;Marchand et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mangrove (21°54′ S, 166°04′ E), covering 20 ha, does not receive any significant freshwater runoff, and was free of anthropogenic influences. This forest exhibits the typical zonation of mangroves in New Caledonia [18]: (i) at the back side of the mangrove swamp, the area is occupied by the salt-flat, a highly saline zone, only submerged during high spring tide and covered sporadically in the most downstream stretches with bushes of Sarcocornia quinqueflora; (ii) a second stand of vegetation, downstream, is occupied by Avicennia marina; (iii) finally, the seaward edge is occupied by Rhizophora stylosa, which is submerged at each tide. Tides are semidiurnal, and mangroves were fully drained at each low tide, except during neap tides where parts of the Rhizophora area remain flooded.…”
Section: Study Sitementioning
confidence: 99%
“…In New-Caledonia, mangrove forests are developed over 35,000 ha, fringing on about 80% and 15% of the western and the eastern coastline of the island, respectively [16]. Previous studies [17,18] suggested that the main factor controlling the distribution of mangrove species in New Caledonia was soil salinity, which in turn was controlled by the duration of tidal inundation and thus by the soil elevation [19]. Thus, our hypothesis are that towards the sea-side: (i) the sediment will be enriched in organic matter because of higher productivity resulting from less stressing conditions; (ii) the sediments will be more reducing because of longer waterlogging and higher organic content; (iii) and the concentrations of key nutrients will be lower because of plant uptake.…”
Section: Introductionmentioning
confidence: 99%